Adapted Taekwondo Improves Postural Balance and Health-Related Quality of Life Concerning Multicomponent Training and Walking Exercise in Older Females: A Randomized Controlled Trial (Tkd and Aging Project) - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background/Objectives: This study aimed to assess and compare the effects of an adapted taekwondo (TKD) program, multicomponent training (MCT), walking exercise (WE), and inactive control group (CG) on blood pressure, morphological variables, frequency of food consumption, cognitive status, health-related quality of life (HRQoL), physical fitness tests, and postural balance in independent older females. Methods: A randomized controlled trial study was conducted with the following groups: TKD (n = 13), MCT (n = 12), WE (n = 12), and CG (n = 14), considering three/weekly 60-min/sessions for 16-weeks. A two-factor mixed analysis of the variance model with repeated measures was performed. Results: TKD improved significantly more in phonetic fluency (p = 0.021; ES = 1.89) than WE and in general health (p = 0.033; ES = 1.11) than CG. Both TKD and MCT improved significantly more than CG in the 30 s chair stand, arm curl, chair sit-and-reach, timed up-and-go, maximal isometric handgrip strength, and postural balance for the eyes closed condition in the area and anteroposterior velocity (p < 0.05). Conclusions: Only TKD improved the area (p = 0.008; ES = 1.00) and mediolateral velocity (p = 0.019; ES = 0.79) for the eyes open condition, and mediolateral velocity (p = 0.021; ES = 1.57) for the eyes closed condition. Blood pressure, morphological variables, and food consumption frequency showed no significant intragroup or intergroup interactions. TKD equivalently improved HRQoL and physical fitness to MCT, with better postural balance in older females. © 2024 by the authors.